Effect of livefood organisms on the growth and gonadal maturation of goldfish (Carassius auratus) - Ahilan, B; Kumaran, R (Indian Journal of Fisheries, 2011)
The investigation was aimed at determining the effect of livefood organisms on the growth and maturation of goldfish. Artemia fed fishes recorded highest mean weight gain. The individual mean weight gain of a fish per day was recorded to be 0.043g for adult goldfish fed with Artemia, 0.025g for the earthworm fed fishes and 0.023g in control. Growth rate was almost double in Artemia fed fishes than control. The highest GSI values for both sexes were also recorded in Artemia fed fishes followed by those fed with earthworm.